ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL BILANGAN PECAHAN BERDASARKAN TIPE KESALAHAN NOLTHING KELAS V SE-GUGUS 1 KECAMATAN TAMPAN KOTA PEKANBARU - Siti Sarah; Gustimal Witri; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research is motivated by many students who find it difficult to understand the meaning of fractions and operations. So that students have difficulty in solving fraction problems that have an impact on errors in working on fraction problems. By knowing the mistakes made by students, it is expected that the teacher can make appropriate improvements in the teaching and learning process. The research aims to find out the students' mistakes in solving fractions based on the type of Nolthing error. The method used in this research is quantitative descriptive. This research was conducted in several elementary schools which are included in a cluster of 1 Tampan sub-district, Pekanbaru City. The sample in this study amounted to 42 students. After conducting research and analysis of data, conclusions can be obtained that the mistakes made by students, namely, errors misinterpreting the instructions (misread directions errors) which amounted to 34.82%, then conceptual errors ((consept errors) amounted to 23.80%, errors in carelessness (carreles errors) of 18.16%, test-taking errors amounted to 11.31% and the last application errors (application errors) were 2.08%. The rest of the students answered the fraction correctly at 9.82 %Keywords: Mathematics, Fractional Problems, Nolthing Errors